Lived Islamic Parenting and Child Resilience in Muslim Families with High Maternal Work Mobility: A Qualitative Study in Islamic Education - Corona, Cisca; Kurnia Jayadinata, Asep; Ardiyanti, Dhea (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2025)
Purpose – This study analyzes how lived Islamic parenting is practiced by Muslim mothers with high work mobility and how these practices contribute to early childhood resilience in urban Muslim families. Transnational family literature is used as a conceptual lens to understand constraints on physical presence and the maintenance of communication, not to equate the migration context. Design/methods/approach – This interpretive qualitative study used a multiple case study design involving Muslim families in an urban area of West Java (pseudonymized). Participants consisted of 10 mothers with children aged 3 to 6 years, selected through criterion-based purposive sampling; sample adequacy was justified using the principle of information power. Data were collected through semi-structured in-depth interviews (45 to 60 minutes) and observations focused on moments of mother-child interaction (for example, after returning from work and before bedtime), as well as non-sensitive supporting materials if agreed upon. Analysis was conducted using reflexive thematic analysis and cross-case synthesis. Findings – The analysis produced four themes. First, Islamic parenting practices are sustained through micro routines at transition moments, primarily role modeling and the habituation of worship practices that are concise and flexible. Second, religious socialization occurs through the maintenance of emotional presence, including consistent long-distance communication and the use of value language (sabar, adab, doa) when responding to children’s emotions. Third, resilience appears as recovery after pressure or failure when affective support is prioritized, after which simple religious routines are used to soothe and encourage children to try again and to express feelings. Fourth, fatigue, time constraints, and digital exposure drive the negotiation of practices through minimum routines and value-based device accompaniment. Research implications – The findings support the design of value-based micro routines at transition moments, the use of Islamic moral vocabulary for emotion coaching preceded by affective support, consistent long-distance communication to maintain continuity of value socialization, and digital parenting through accompaniment, restriction, brief explanations, and content redirection in early childhood education.